1998
DOI: 10.1159/000044989
|View full text |Cite
|
Sign up to set email alerts
|

The Fibronectin Production Is Increased by Thrombospondin via Activation of TGF-β in Cultured Human Mesangial Cells

Abstract: Thrombospondin (TSP) is a multifunctional glycoprotein that is synthesized by a variety of cells including mesangial cells (MCs). To clarify the effect of TSP on the pathogenesis of diabetic nephropathy, we studied the effect of glucose concentrations on TSP synthesis in cultured human MCs. Thereafter, the effects of TSP on the activation of transforming growth factor beta (TGF-β) and fibronectin production were investigated in MCs. Incubating MCs with elevated glucose levels for 6 days resulted in an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…Differential expression of 15 of the 16 subcloned fragments was confirmed by Northern blot (Table I). Sequence analysis revealed induction of four genes implicated previously in the pathogenesis of diabetic nephropathy: fibronectin, caldesmon, plasminogen activator inhibitor-1 (PAI-1), and thrombospondin (15)(16)(17)(18). Of 11 other cDNA fragments, two encoded novel genes, designated IHG-1 and IHG-2 (increased in high glucose), and nine encoded known genes whose induction by high glucose had not been reported previously.…”
Section: Ssh Identifies 15 Mesangial Cell Genes Differentiallymentioning
confidence: 79%
“…Differential expression of 15 of the 16 subcloned fragments was confirmed by Northern blot (Table I). Sequence analysis revealed induction of four genes implicated previously in the pathogenesis of diabetic nephropathy: fibronectin, caldesmon, plasminogen activator inhibitor-1 (PAI-1), and thrombospondin (15)(16)(17)(18). Of 11 other cDNA fragments, two encoded novel genes, designated IHG-1 and IHG-2 (increased in high glucose), and nine encoded known genes whose induction by high glucose had not been reported previously.…”
Section: Ssh Identifies 15 Mesangial Cell Genes Differentiallymentioning
confidence: 79%
“…49 TSP1 increases fibronectin expression by cultured renal tubular epithelial cells through TGF-␤-dependent and independent mechanisms 58 and also in glucose-treated mesangial cells through a TGF-␤-dependent mechanism. 50 Blockade of CD36 through RNA silencing in cultured renal proximal tubular cells reduced bioactive TGF-␤1 and fibronectin in the presence of profibrogenic concentrations of albumin. 59 Together, these data suggest that TSP1-mediated activation of latent TGF-␤ is a key factor in diabetic tubulointerstitial fibrosis and proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Furthermore, TSP1 increases fibronectin expression by cultured mesangial cells in a TGF-␤-dependent manner. 50 Therefore, the effects of LSKL treatment on renal fibronectin expression were examined by immunostaining of renal sections and by immunoblotting of renal lysates. Immunoblotting of renal lysates from high-dose LSKL-treated mice showed a Ͼ66% reduction in fibronectin expression (Figure 2).…”
Section: Lskl Treatment Reduces Renal Injurymentioning
confidence: 99%
“…TSP1, a disulfide-linked 180-kDa trimer, is a multifunctional protein that is produced by a variety of cells, including mesangial cells. In vitro and in vivo studies show that high glucose up-regulates TSP1 expression (13)(14)(15)(16)31) and that TSP1 protein is increased in the kidneys of diabetic patients (17). Recently, we and others showed that TSP1 is responsible for the activation of TGF-␤ in mesangial cells when exposed to high glucose for either short (2 days) or long term (3 weeks) treatment (18,19).…”
mentioning
confidence: 99%